Social Unrest in Democracy: Political Alienation, Socio-Emotional Climate and Legitimacy - Alonso, Daniela; Brussino, Silvina (Revista de Psicología, 2021)
Democracy is experiencing a conflictive time in Latin America, expressed in decreasing levels of political legitimacy and an increase in the discontent and malaise of citizens. In this framework, we analysed the local political culture through dimensions of political alienation and emotional social climate as means for describing political well-being. In addition, we studied the role of political culture variables in predicting the social climate, emphasising its ideological component. Finally, we addressed the relationship between the perception of the social climate and democratic legitimacy. We conducted a survey-based quantitative study. We took a quoted population sample of 450 people (59.1% women, M age = 33.7 years). Our results evidenced high levels of political cynicism and perception of anomie, low levels of political confidence, integration and social and political participation and a negative balance of social climate, being compatible with a political culture characterized by alienation. In addition, the variables relative to political alienation were significant predictors of the social climate perception and, in addition, voter choice and ideological dimensions intervened. Finally, social climate differentially predicted general and specific attitudes towards democracy and the current political system.